Connecting : healing for ourselves and our relationships : a radical new vision - Crabb, Larry, 1944- (Nashville,. Tenne W Publishing Group, a division of Thomas Nelson, Inc, 1997)
In this groundbreaking work, Larry Crabb shows readers how to build intimate, healing connections with others - mini-communities where God's power to heal souls is quickened and released through individuals' compassionate, authentic relationships with others.
Introduction: A shift in my thinking -- Kep's story -- Three ingredients of healing community -- Restored through reconnecting -- Designed to connect -- Connecting: The center of life -- Connection and vision -- Vision in the highest -- What's good about us? -- The enemy within -- Dying together to live together -- Urges to be killed -- Two more urges to be killed -- Connecting in the heat of battle -- It's time to connect -- Entering the real battle -- Developing a vision -- Releasing the energy -- Epilogue -- Appendix A: The talking cure does not belong only to professionals -- Appendix B: A word to professional counselors and church leaders.
Keywords: Interpersonal relations -- Religious aspects -- Christianity